Design and Construction of Microwave-Assisted Pyrolysis of Waste Coconut Shell for the Isolation of Pyroligneous Acid - Kusumaningtyas, Ratna Dewi; Prasetiawan, Haniif; Astuti, Widi; Pita Rengga, Wara Dyah; Aji Muhammad, Dimas Rahadian (KnE Social Sciences, 2019)
As a country with a large amount of natural resources, Indonesia should be able to convert this material into more value added product. However, most of the natural resources were sold as a raw material. Process system engineering research center is one of the solution to overcome this problem by developing an integrated and systematic technology. Through this research center, output of the research can be scaled up for large scale production and also can be commercialized to increase the community welfare. One of natural resources which has not been optimally utilized is waste coconut shell (WCS). Indonesia is the largest coconut producer in the world with areal production of 3.88 ha and 3.2 million ton of coconut products. Several problems arefacedbycoconutagroindustry,i.e.thelackofcoconutbasedproductdiversiﬁcation and also the large number of WCS. WCS is one of organic waste, however it is quite hard to be decomposed by the microorganism due to its hard texture. This problem may gave high potential in the environmental pollution. In this research, WCS is going to be used as a raw material for pyroligneous acid through pyrolysis process. Pyrolysis is a method that is usually used to convert a biomass waste sources into a valuable product through thermal decomposition process without the presence of oxygen. This process will produce solid (char), liquid (bio-oil, tar and pyroligneous acid) and gas. Pyroligneous acid is commonly obtained as a side product from the production of active carbon and to date it has not been utilized economically. In the other hand, pyroligneous acid can be used as an anti-oxidant, antimicrobial, antifungal, anti-bioﬁlm and also as an anti inﬂammatory. This properties are available due to the presence of organic matter and phenolic compound in the pyroligneous acid. This characteristics showedthatpyroligneousacidishighlypotentialasrawmaterialindrugsandpharmacy industries. Pyrolysis process requires high temperature which has range between 500 – 600 ∘C. In this paper, it will be discussed a pyrolysis equipment design and productionofpyroligneousacidfromWCSbyusingmicrowave-assistedpyrolysis(MAP). Keywords: Coconut Shel, Pyroligneous Acid, Pyrolysis, Microwave, Pharmacy